Congenital or acquired? Obstructive jaundice in reoperated duodenal atresia. Issue 8 (28th August 2019) - Goh, Mervin Feng Ji; Mak, Malcolm Han Wen; Low, Yee; Ong, Caroline Choo Phaik
Abstract : A 55-day-old boy was transferred to our unit with intestinal obstruction and obstructive jaundice after two neonatal operations for duodenal atresia and intestinal malrotation. Abdominal ultrasound showed dilated intrahepatic and extrahepatic ducts with cut-off at the distal common bile duct (CBD). He underwent emergency laparotomy for adhesive intestinal obstruction with a contained abscess from mid-jejunal perforation. Biliary dissection was not attempted due to poor preoperative nutritional status. Tube cholecystostomy was created for biliary decompression. Postoperative magnetic resonance cholangiopancreatography showed dilated CBD with cut-off at the ampulla but did not demonstrate pancreaticobiliary maljunction (PBMJ). The diagnostic dilemma was whether our patient had congenital PBMJ or had developed biliary stricture from perioperative ischaemic scarring. He underwent definitive surgery at 7 months: excision of dilated CBD with Roux-en-Y hepaticojejeunal reconstruction, excisional tapering duodenoplasty and jejunostomy creation. Intraoperative finding was type I choledochal cyst and subsequently confirmed on histology. Postoperative recovery was uneventful and bilirubin levels normalised.